Rancangan Sistem Informasi Inventory Penjualan Berbasis Web Pada Toko Yuda Pasar Inpres Kecamatan Kelapa Gading - Widiatma, Christian Agung; Abdillah, Lufty (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2025)
The development of increasingly advanced technology makes business actors have to follow developments that occur in the entrepreneurial environment. In this research, we do a website-based inventory design at Toko Yuda. The inventory system in the store is still done manually, so this study aims to build an inventory system at Yuda Stores web-based, to cover the process of incoming goods, outgoing goods, recording. The research method used is the development of a prototyping system that includes system analysis using cross-functional diagrams. The modeling in this system uses the Unified Modeling Language (UML), this development system is built with a MySQL database and PHP programming and using Black Box testing. The purpose of this system is to make it easier for users to record inventory activities at Yuda's store and print goods reports. The result of this research is that the system has been successfully built based on the design of business requirements and provides functions that facilitate the storage process.